MENGGUNAKAN MODEL PEMBELAJARAN DEBAT AKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN AGAMA KATOLIK DI SMPN 41 MEDAN - Nani Parangin Angin (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to increase students' learning motivation with an active debate learning model in the field of Catholic religious studies with the topic "Dating" at SMPN 41 Medan. This study uses a classroom action research (CAR) design which consists of 2 cycles and 4 stages, namely: planning, implementation, observation and reflection stages. The subjects of this study were all students of SMPN class VII who were Catholic as many as 16 people. The results of the research descriptively, showed that students' learning motivation has increased continuously. It was proven that the students' learning motivation before the action got an average score of 2.20 with a medium category, after the action in the first cycle got an average score of 2.85 with a good category, and after the action in the second cycle it got an average value of 3 .55 with very good category. Furthermore, the results of data analysis regarding the use of the active debate learning model also experienced continuous improvement. It is also proven that the use of the active debate learning model after the action in the first cycle obtained an average score of 2.70 with a good category, and after the action in the second cycle it increased to very good with an average value of 3.38. Based on the results of this study, it can be concluded that the use of an active debate learning model can increase the learning motivation of class VII students of SMPN 41 Medan.